Strengthening the Communication System of the Interfaith Harmony Forum (FKUB) in Serdang Berdagai - Zahra, Fatimah; Sazali, Hasan (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to investigate the improvement of the FKUB communication system in Serdang Bedagai. This study uses a descriptive qualitative methodology. This study uses interpersonal communication theory, which emphasizes the importance of face-to-face interaction and touch between individuals in transmitting messages, building relationships, and promoting mutual understanding. The findings of the study indicate that: 1) FKUB in Serdang Bedagai functions as an institution that fosters religious harmony and actively promotes unity among diverse religious communities. FKUB was established through collaborative community initiatives and government support with the aim of building, preserving, and empowering religious groups to promote harmony and prosperity. 2) Efforts by FKUB Serdang Bedagai to promote religious harmony: FKUB collaborates and forms agreements with people who act as guardians of harmony and religious authorities from various regions, with a special emphasis on Dolok Masihul District. The guardians of harmony work together with religious adherents, harmony authorities at the village level, and government officials, including the local police. 3) Improving the FKUB Communication System: As an institution that promotes interfaith harmony, FKUB is actively involved in discussions with religious and community leaders, and effectively facilitates and channels the aspirations of religious and community groups. This responsibility requires an efficient communication process, which involves various components that must be actively involved so that the communication process can run well.